PYROXENE AND GARNET MEGACRYSTS IN THE MAGMATIC SYSTEM AND MANTLE OF THE TESIINGOL VOLCANIC FIELD IN NORTHERN MONGOLIA - A. P. Zhgilev; A. B. Perepelov; S. S. Tsypukova; Yu. D. Shcherbakov; A. A. Karimov (Геодинамика и тектонофизика, 2025)
Studies have been made on pyroxene (Cpx) and garnet (Grt) megacrysts from the rocks related to two-stage formation of the Tesiingol volcanic field in Northern Mongolia. The rocks related to the initial stage of the volcanic field formation, basanites and phonotephrites of the Early Miocene Bod-Uul volcano (40Ar/39Ar, 17.0±0.5 Ma), do not contain xenogenic material. Megacrysts and associated peridotite and pyroxenite xenoliths were discovered in eruptive deposits and lavas of basaltic trachyandesites of the Middle Miocene Uguumur volcano (40Ar/39Ar, 12.5±0.2 Ma) at the second stage of activity. The volcanic field rocks show the presence of carbonate matter. Cpx and Grt megacrysts have traces of melting and transformation and are associated with sanidine, ilmenite and apatite megacrysts. Pyroxenes have elevated contents of Al and Na and are similar in composition to omphacites (Di71–72Jd16–19Ae9–12). Garnets are characterized by chromium-free almandine-grossular-pyrope composition (Alm58–66Grs17–20Pyr14–19) and correspond to minerals of eclogite paragenesis. Pyroxene megacrysts, compared in composition to pyroxenes from eclogites and peridotites, are enriched in REE, Y, Nb, Ta and Hf. Garnets show relatively high contents of LREE, Zr and Hf. It has been found that the early-stage basanite and phonotephrite magmas were formed in the asthenospheric mantle at 21–28 kbar and 1359–1432 °C. The formation of basaltic trachyandesite melts occurred near the crust and upper mantle at 10–13 kbar and 1192–1237 °C. Megacrysts of the Cpx+Grt association crystallized at 20–24 kbar and 1190–1331 °C in the area of the garnet facies of the lithospheric mantle depth and near its boundary with the asthenosphere. Based on the data for P-T formation conditions, crystal chemistry, trace element and isotopic composition of Cpx and Grt megacrysts, a model of the origin of the latter has been proposed. It is suggested that megacrysts formed above the deep magma chamber as a result of the process similar to pneumatolytic, due to the separation and subsequent crystallization of a silicate-carbonate phase above the solidus of carbonated peridotites, mainly in the lithospheric mantle.